DEIKSIS DALAM PIDATO NELSON MANDELA SAAT DIBEBASKAN DARI PENJARA DAN SAAT PELANTIKANNYA SEBAGAI PRESIDEN AFRIKA SELATAN - DEMMATANDE, ANDRIS (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTThis research is entitled ?A Deixis Analysis in Selected Nelson Mandela?s Speeches?. In this research the writer focuses on deixis in the speeches. The speeches of Nelson mandela was famous in the last of 20th century. Those speech are: Nelson Mandela?s speech after his release from prison and Nelson Mandela?s speech at his inauguration as a president of South Africa. The purpose of this research are to identify and classify the types of deixis and to analyze the usage of deixis in Nelson Mandela?s Speeches. The data were analyzed based on Levinson?s theory (1983) there are 5 types of deixis, those are: person deixis (first person, second person, third person), place deixis, time deixis, discourse deixis, and social deixis. Deixis belongs to pragmatic. It means ?pointing?.The results of this research show that there are five types of deixis in Nelson Mandela?s Speeches, those are person deixis (first person: I, we, my, myself us, our, ourselves; second person : you, your; and third person : they, it their, his own, himself), places deixis : here, this city, this country this stage, come, this common homeland, this land, time deixis: today, lasted too long, when, back, not so long ago, the time, the moment, three decades, the darkest day in history, on this occasion, 40 years, long and lonely years, the past few years, remaining years of my life, this day, discourse deixis : this and it, and social deixis: your majesties, your highness, my comrades, friends, all political prisoner, the traditional leader, fellow South African, black and white, the masses, distinguished international guest. Additionally, deixis that mostly appears on Nelson Mandela?s speech after his release from prison is first person deiksis ?I? represents Nelson Mandela as a leader who govern black South African  whereas at the second speech deixis that mostly appears on Nelson Mandela?s speech at his inauguration as a president of South Africa is first person deixis ?we? representing that all of South African were united.Keywords : Pragmatic, Deixis, Speech, Nelson Mandela